Potential impact of macroclimatic variability on the epidemiology of giardiasis in three provinces of Cuba, 2010-2012 - Angel A. Escobedo; Pedro Almirall; Raisa Rumbaut; Alfonso J. Rodríguez-Morales (Elsevier, 2015)
Summary: Climate change and variability are common phenomena affecting various infectious diseases. Many studies have been performed on vector-borne diseases; however, few studies have addressed such influences on intestinal parasitic diseases (e.g., giardiasis). In this study, using nonlinear Poisson regression models, we assessed the potential associations between macroclimatic variation and giardiasis cases in children and school workers from three provinces of Cuba in the context of large sampling and parasitological assessment. Between 2010 and 2012, 293,019 subjects were assessed, resulting in 6357 positive for Giardia (216.95 cases/10,000 pop.; 95%CI 211.7-222.2). The variation in time for those giardiasis rates ranged from 35.8 to 525.8 cases/10,000 pop. Nonlinear Poisson regression models between the ONI index and the giardiasis incidence indicated a significant association (p < 0.01). With lower values of ONI, lower incidence of giardiasis was observed at Havana (pseudo r2 = 0.0576; p < 0.001) and Guantánamo (pseudo r2 = 0.0376; p < 0.001). Although these results are preliminary and the magnitude of association is not higher, the results were of statistical significance. This result indicates the need to assess in detail in further studies the impact of additional macroclimatic and microclimatic variables on the epidemiology of this still important intestinal parasitic disease, not only in Cuba but also in other countries of the Caribbean and Latin American region. Keywords: Giardiasis, Ecoepidemiology, Climate Change, Cuba